2017
DOI: 10.1161/atvbaha.116.308749
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Specific Deficiency of NADPH Oxidase 4 Delays the Onset of Insulin Resistance and Attenuates Adipose Tissue Inflammation in Obesity

Abstract: Objective Obesity is associated with insulin resistance and adipose tissue inflammation. Reactive oxygen species (ROS) increase in adipose tissue during the development of obesity. We previously showed that in response to excess nutrients like glucose and palmitate, adipocytes generated ROS via NADPH oxidase (NOX) 4, the major adipocyte isoform, instead of using mitochondrial oxidation. However, the role of NOX4-derived ROS in the development of whole body insulin resistance, adipocyte inflammation, and recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 34 publications
3
88
0
Order By: Relevance
“…15,16 In line with this concept, using adipocyte-specific NADPH (nicotinamide adenine dinucleotide phosphate) oxidase 4-deficient mice, Den Hartigh et al 17 demonstrated that adipocyte NADPH oxidase 4-derived ROS contributed to the development of obesityrelated insulin resistance by triggering adipocyte inflammation. La Favor et al 18 developed a novel microdialysis technique that enables simultaneous measurement of ROS levels and microvascular endothelial functions in vivo.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 96%
“…15,16 In line with this concept, using adipocyte-specific NADPH (nicotinamide adenine dinucleotide phosphate) oxidase 4-deficient mice, Den Hartigh et al 17 demonstrated that adipocyte NADPH oxidase 4-derived ROS contributed to the development of obesityrelated insulin resistance by triggering adipocyte inflammation. La Favor et al 18 developed a novel microdialysis technique that enables simultaneous measurement of ROS levels and microvascular endothelial functions in vivo.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 96%
“…NOX4-induced ROS will further stimulate the increase in the expression of chemotactic factors in cultured adipocytes that was reversed upon silencing of Nox4 [134]. Moreover, in diet-induced obese mice, specific deletion of Nox4 protects from nutrient-induced adipose inflammation and the early onset of insulin resistance [135]. It was shown that upon Nox4 deletion in adipocytes, there was a down-regulation in the expression of macrophage chemotactic factor genes Saa3 and Ccl2, mRNA expression of macrophage markers (Mac2, Cd11b, Cd11c, and Emr1), Mac2 protein, as well as expression of the pro-inflammatory cytokines IL-6 and TNF-α [135].…”
Section: The Cross-link Between Nadph Oxidases-induced Oxidative Strementioning
confidence: 99%
“…Moreover, in diet-induced obese mice, specific deletion of Nox4 protects from nutrient-induced adipose inflammation and the early onset of insulin resistance [135]. It was shown that upon Nox4 deletion in adipocytes, there was a down-regulation in the expression of macrophage chemotactic factor genes Saa3 and Ccl2, mRNA expression of macrophage markers (Mac2, Cd11b, Cd11c, and Emr1), Mac2 protein, as well as expression of the pro-inflammatory cytokines IL-6 and TNF-α [135]. In streptozotocin-induced ApoE − / − diabetic mice, deletion of Nox4, but not of Nox1, ameliorated kidney injury.…”
Section: The Cross-link Between Nadph Oxidases-induced Oxidative Strementioning
confidence: 99%
“…27,60,61 Although some studies have provided evidence for the protective effect of Nox4, 62,63 others have reported Nox4-mediated ROS as a molecular switch promoting the differentiation of preadipocytes, the onset of insulin resistance, and adipose tissue inflammation. 60,[64][65][66] Additionally, increased expression of Nox4 in white adipose tissue can result in the production of H 2 O 2, which can be converted to • OH radicals via the Fenton and Haber-Weiss reactions in the presence of Fe 2+ and Cu 2+ ions, eventually leading to oxidative DNA damage. 27 Weyemi et al 67 disease (NAFLD) and hepatocellular carcinoma (HCC).…”
Section: Obesity-induced Oxidative Stress Promotes Dna Damagementioning
confidence: 99%